Damage assessment of low to mid rise reinforced concrete buildings considering planner irregularities. Issue 2 (13th December 2020) - Hait, Pritam; Sil, Arjun; Choudhury, Satyabrata
Abstract: Structural damage index (SDI) is determined to implement damage-based design (DBD) which is a useful design philosophy in terms of safety and reliability nowadays. Literature is available to determine DI using different methods. Park-Ang damage assessment method is popular among them. In this method, first member damage is calculated then storey damage index is determined. From the calculated SDI, global damage index (GDI) is estimated. Park-Ang method requires three steps to estimate DI of structure which is tedious and time-consuming procedure for a multi-storied building. To avoid this complexity, a simplified DI model has been proposed which can estimate global DI directly. In the proposed model, three most influential engineering demand parameters (EDPs) have been combined to estimate GDI directly. For this purpose, 27 typical samples of 4-, 8-, and 12-storey reinforced concrete (RC) buildings with rectangular-shape, L-shape, and U-shape planner geometry were considered to account the effect of planner irregularities. It has been found that the proposed model established a good agreement with Park-Ang DI. The proposed model effectively estimates reliable GDI and can be used as a powerful tool for estimating seismic damage of buildings especially for massive structures.